Specimen insurance forms and glossaries - Dinsdale, W. A. (London : Stone & Cox Ltd., 1963)
Unlike the first edition, some additional proposal and policy forms have been included, and various terms have been added to the glossaries. Where necessary, forms have also been brought up to date.
ne 16/05/2018
Loans
Keywords: Insurance